The Effect of Air Pollution on Fertility Intentions - Li, Yunrong (Problemy Ekorozwoju, 2021)
Together with fast economic growths in recent decades and subsequent environmental pollutions, fertility rates have declined dramatically in China. Considering fertility intention is an essential predictor for fertility rate, we examine the effect of air pollution on fertility intentions in China. Using data from the China General Social Survey (CGSS) collected in 2010 and 2013, we find a negative and significant impact of air pollution on people’s fertility intentions. More importantly, after we restrict the sample to people who have been living in current places for a long period of time, the estimated effect of air pollution decreases but remains significant, indicating existence of endogeneity of air pollution on fertility intentions. For the government to take measures to raise fertility rates in China, it is important to take into account the factor of air pollution.